Activation of the p62‐Keap1‐NRF2 pathway protects against ferroptosis in hepatocellular carcinoma cells. Issue 1 (26th November 2015) - Sun, Xiaofang; Ou, Zhanhui; Chen, Ruochan; Niu, Xiaohua; Chen, De; Kang, Rui; Tang, Daolin
Abstract : Ferroptosis is a recently recognized form of regulated cell death caused by an iron‐dependent accumulation of lipid reactive oxygen species. However, the molecular mechanisms regulating ferroptosis remain obscure. Here, we report that nuclear factor erythroid 2‐related factor 2 (NRF2) plays a central role in protecting hepatocellular carcinoma (HCC) cells against ferroptosis. Upon exposure to ferroptosis‐inducing compounds (e.g., erastin, sorafenib, and buthionine sulfoximine), p62 expression prevented NRF2 degradation and enhanced subsequent NRF2 nuclear accumulation through inactivation of Kelch‐like ECH‐associated protein 1. Additionally, nuclear NRF2 interacted with transcriptional coactivator small v‐maf avian musculoaponeurotic fibrosarcoma oncogene homolog proteins such as MafG and then activated transcription of quinone oxidoreductase‐1, heme oxygenase‐1, and ferritin heavy chain‐1. Knockdown of p62, quinone oxidoreductase‐1, heme oxygenase‐1, and ferritin heavy chain‐1 by RNA interference in HCC cells promoted ferroptosis in response to erastin and sorafenib. Furthermore, genetic or pharmacologic inhibition of NRF2 expression/activity in HCC cells increased the anticancer activity of erastin and sorafenib in vitro and in tumor xenograft models. Conclusion: These findings demonstrate novel molecular mechanisms and signaling pathways of ferroptosis; the status of NRF2 is a key factor that determines the therapeutic response to ferroptosis‐targeted therapies in HCC cells. (Hepatology 2016;63:173–184)